Potential Metabolic Drug–Drug Interaction of Citrus aurantium L. (Rutaceae) Evaluating by Its Effect on 3 CYP450 - Zhou, Lu; Cui, Man; Zhao, Linlin; Wang, Dongsheng; Tang, Tao; Wang, Wenbo; Wang, Sheng; Huang, Huiyong; Qiu, Xinjian (Frontiers in Pharmacology, 2018)
Background: Fructus Aurantii (FA) is widely used in clinic as an expectorant and digestant herb in traditional Chinese medicine and proven to have a variety of pharmacological functions. FA is close to grapefruit either by botanical taxonomy or by their same components (flavonoids, etc.) and grapefruit has been proven to cause drug-drug interaction when co-administrated with CYP3A4 substrates. Besides, FA contains many compounds, such as flavonoids, which have been reported to impact the expressions of CYP450. However, the effect of FA on CYP450, whose change may affect drug safety and clinical efficacy attributed to drug-drug interaction, still remains unknown. Material and method: The protein, mRNA expression and enzyme activity of CYP1A2, CYP3A4 and CYP2E1 in rat were determined by Western Blotting, RT-PCR method, the cocktail method, respectively, after orally administration of FA in succession for 7 days. CYP1A2, CYP3A4 and CYP2E1 mRNA expression were investigated in HepG2 cells following FA-medicated serum incubation for 24h. Result: In rat, compared to the control group, CYP1A2, CYP3A4 protein and mRNA expression were significantly induced consistent with the corresponding CYP activities; the protein expression of CYP2E1 was significantly up-regulated, while the corresponding mRNA expression and enzyme activity showed no significant change. In HepG2 cells, compared to the control group, the mRNA expression of CYP1A2 and CYP3A4 was up-regulated statistically while CYP2E1 mRNA expression was not significantly induced or inhibited. Conclusion: FA may be a potential slight inducer of CYP1A2 and CYP3A4 and is unlikely to impact CYP2E1 until clinical researches are conducted.